Pengaruh Penggunaan Model Contextual Teaching And Learning (CTL) Terhadap Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran Akidah Akhlak di MTSs Yati Kamang Mudik - Lutfiyah Rahmi; Supriadi Supriadi; Hamdi Abdul Karim; Nurhasnah Nurhasnah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The background of this research is that the model used by the teacher is not appropriate with the learning needs of students at MTsS Yati Kamang Mudik, the level of critical thinking of students seems less active in expressing opinions, not giving many suggestions or questions, not being able to explain problems, with the influence of the social environment. This research is a quantitative study. The research design used is Quasi-Experimental. The sample for this study was class VII students at MTsS Yati Kamang Mudik with a sample size of 40 students. The research samples were class VII-1 experimental using the Contextual Teaching and Learning model and class VII-2 control using the conventional model. Data analysis techniques used the Normality Test with the Kolmogorov Smirnov formula, and homogeneity test with Fisher's test followed by hypothesis testing with Independent t-test. The results of the study show that based on the results of data processing it can be concluded that there is a significant influence on the use of the Contextual Teaching and Learning (CTL) model as these results prove that the value of the experimental class Sig. (2-tailed) = 0.001. While the research alpha = 5% or 0.05. That is, the value of Sig. (2-tailed) is greater than the alpha value (0.001 <0.05) so that there is an influence of the Contextual Teaching and Learning (CTL) learning model on students' critical thinking skills in the Akidah Akhlak lesson at MTsSYati kamang Mudik in class VII.